2012
DOI: 10.1016/j.immuni.2012.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Ameliorate Autoimmunity in the CNS by Controlling the Homeostasis of PD-1 Receptor+ Regulatory T Cells

Abstract: Mature dendritic cells (DCs) are established as unrivaled antigen-presenting cells (APCs) in the initiation of immune responses, whereas steady-state DCs induce peripheral T cell tolerance. Using various genetic approaches, we depleted CD11c(+) DCs in mice and induced autoimmune CNS inflammation. Unexpectedly, mice lacking DCs developed aggravated disease compared to control mice. Furthermore, when we engineered DCs to present a CNS-associated autoantigen in an induced manner, we found robust tolerance that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
182
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(203 citation statements)
references
References 50 publications
16
182
0
3
Order By: Relevance
“…Moreover, in agreement with data reporting PD-L1 as necessary for the DC-mediated induction of Treg cells (24) and tolerance, our results indicate that HGF treatment significantly increases PD-L1 expression by DCs. Although these immunomodulating mechanisms may confer the regulatory properties of HGF-treated DCs, it does not provide the molecular mechanisms by which HGF generates tolerogenic DCs.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in agreement with data reporting PD-L1 as necessary for the DC-mediated induction of Treg cells (24) and tolerance, our results indicate that HGF treatment significantly increases PD-L1 expression by DCs. Although these immunomodulating mechanisms may confer the regulatory properties of HGF-treated DCs, it does not provide the molecular mechanisms by which HGF generates tolerogenic DCs.…”
Section: Discussionsupporting
confidence: 92%
“…Another aspect that argues against a general interference with T cell responses by B7-H1 is the selective promoting effect of B7-H1-Ig on murine TGF-bmediated inducible T reg (iT reg ) differentiation, in line with other studies (30,45,46). However, it has been reported that induction of iT reg generation and function by B7-H1 is mediated via PD-1 (30,46). Hence although our data set provides clear evidence for the presence of a novel non-PD-1 receptor executing B7-H1 effects on T H 17 differentiation, other studies complementarily illustrate that under certain conditions such as presence of steadystate dendritic cells or under suboptimal stimulatory conditions, B7-H1-PD-1 interaction is also involved in the modulation of T cell differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…This result was unexpected, because several studies proposed that this pathway primarily affects generation of IFN-g-producing T H 1 cells (41)(42)(43)(44). Another aspect that argues against a general interference with T cell responses by B7-H1 is the selective promoting effect of B7-H1-Ig on murine TGF-bmediated inducible T reg (iT reg ) differentiation, in line with other studies (30,45,46). However, it has been reported that induction of iT reg generation and function by B7-H1 is mediated via PD-1 (30,46).…”
Section: Discussionmentioning
confidence: 63%
“…45 Conversely, although the removal of cDCs and pDCs does not result in spontaneous autoimmunity, their removal results in the worsening of EAE and decreased levels of FoxP3 þ Tregs. 46 Taken together, these data suggest that DCs can control peripheral tolerance through their effects on the generation and maintenance of Treg populations under homeostatic and inflammatory conditions. Please note that although it has been postulated that specific DC populations promote the development of FoxP3 þ Tregs 38,40 and Tr1 43 cells in vivo, it is not yet clear whether these populations constitute specific tolerogenic DC lineages or represent alternative activation or maturation states of DCs.…”
Section: Role Of Dcs In the Peripheral Activation Of T Cellsmentioning
confidence: 86%
“…However, the transgenic expression of MHC class II in DCs is sufficient to recover the susceptibility to EAE of otherwise disease-resistant MHC class II-deficient mice. 50 It should also be noted that EAE can be induced in the absence of DCs, 46 indicating that although DCs are sufficient to induce CNS autoimmunity, other APCs can also promote the Figure 1 Classes of DCs. Two major classes of DCs have been identified based on their morphological and functional characteristics: conventional or classical DCs (cDCs) and plasmacytoid DCs (pDCs).…”
Section: Role Of Dcs In the Peripheral Activation Of T Cellsmentioning
confidence: 99%